Efficacy of the 'Five-Needle' method for pancreatojejunostomy in laparoscopic pancreaticoduodenectomy: an observational study - Wang, Zheng-Feng; Zhang, Bo; Xu, Hao; Zhou, Wen-Ce (Frontiers in Oncology, 2024)
Objective The five-needle pancreato-intestinal anastomosis method is used in laparoscopic pancreaticoduodenectomy (LPD). The aim of this study was to explore the clinical efficacy and adverse reactions of this new surgical method and to provide a scientific reference for promoting this new surgical method in the future. Methods A single-centre observational study was conducted to evaluate the safety and practicality of the five-needle method for pancreatojejunostomy in LPD surgeries. The clinical data of 78 patients who were diagnosed with periampullary malignancies and underwent LPD were collected from the 1st of August 2020 to the 31st of June 2023 at Lanzhou University First Hospital. Forty-three patients were treated with the ‘Five-Needle’ method (test groups), and 35 patients were treated with the ‘Duct-to-Mucosa’ method (control group) for pancreatojejunostomy. These two methods are the most commonly used and highly preferred pancreatointestinal anastomosis methods worldwide. The primary outcome was pancreatic fistula, and the incidence of which was compared between the two groups. Results The incidence of pancreatic fistula in the five-needle method group and the duct-to-mucosa method group was not significantly different (25.6% vs. 28.6%, p=0.767). Additionally, there were no significant differences between the two groups in terms of intraoperative blood loss (Z=-1.330, p=0.183), postoperative haemorrhage rates (p=0.998), length of postoperative hospital stay (Z=-0.714, p=0.475), bile leakage rate (p=0.745), or perioperative mortality rate (p=0.999). However, the operative time in the ‘Five-Needle’ method group was significantly shorter than that in the ‘Duct-to-Mucosa’ method group (270 ± 170 mins vs. 300 ± 210 mins, Z=-2.336, p=0.019). Further analysis revealed that in patients with pancreatic ducts smaller than 3 mm, the incidence of pancreatic fistula was lower for the ‘Five-Needle’ method than for the ‘Duct-to-Mucosa’ method (12.5% vs. 53.8%, p=0.007). Conclusion The five-needle method is safe and efficient for pancreatojejunostomy in LPD, and is particularly suitable for anastomosis in nondilated pancreatic ducts. It is a promising, valuable, and recommendable surgical method worthy of wider adoption.